Peranan Enterpreneurship Dalam Pemberdayaan Ekonomi Daerah Sumatera Barat (Kasus Perempuan Pedagang di Pasar Nagari Minangkabau) - Drs. DASRIZAL M.P., DASRIZAL (STKIP PGRI Sumatera Barat, 2011)
Regional autonomy movements understood the desire to get back in the villagegoverment system which is considered “small publichs”. Theeuphoric high that there are issues to be resolved include rebuilding the regionaleconomy through the economis enpowerment of village communities. One ofthem through the village market, which is the birth incubator enterpreneurshipvillage community because there were women’s special merchants in old plants.The group enterpreneur this course contributes to the GDP of West Sumatra.The methodology used in this study is a qualitative approach. Qualitativeapproach is used in explainning the factors that affect women come to trade oldplant that contributes to the economic empowertment of West Sumatra.The result of the study concluded the presence of women traders in thevillage is the birth of the soul of enterpreneurship incubator for the nextgenerations. The involment of women traders in the nagari market unregardless ofeconomic and social problems. The involvement women traders to trade the oldplants, which is one of the sectors contributing to economic growth of WestSumatra. In addition to such other sub palm plantations, rubber, gambier and soforth. This condition is not directly give value of indirect taxes to increase of GDPof West Sumatra’s oil is a commodity of Rp 20.73 billion or 32 %, followed bycoffee at Rp 12.42 billion or by 19 %, tobacco Rp 11.47 billion or 18 %, rubberamounting to Rp Rp 10.21 billion or by 16%. While cassiavera only Rp 2.43billion, or only 4 %, and gambier was Rp 3.53 billion or 5 %.